2015
DOI: 10.1111/aogs.12621
|View full text |Cite
|
Sign up to set email alerts
|

Use of thyroid hormones in relation to pregnancy: a Danish nationwide cohort study

Abstract: Fewer women than expected received levothyroxine treatment during pregnancy even though a fourfold increase was observed during the study period. Furthermore, one of 10 discontinued treatments during pregnancy. These findings all indicate that too few women are treated for hypothyroidism during pregnancy. Further research is needed to determine whether hypothyroid pregnant women are suboptimally treated and the possible consequences for the mother and fetus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Furthermore, the proportion of women who discontinued THRT, as well as the group characteristics of the continuers and discontinuers in the present study, was similar to that reported by Gidén et al . In the crude comparison, discontinuers more often had an unplanned pregnancy than did continuers (24.6% vs. 17.7%).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, the proportion of women who discontinued THRT, as well as the group characteristics of the continuers and discontinuers in the present study, was similar to that reported by Gidén et al . In the crude comparison, discontinuers more often had an unplanned pregnancy than did continuers (24.6% vs. 17.7%).…”
Section: Discussionsupporting
confidence: 89%
“…A recent study in Denmark reported that 1 in 10 women with hypothyroidism discontinued thyroid hormone replacement therapy (THRT) during pregnancy. In a study by Juch et al , 17% of women with hypothyroidism reported low adherence to THRT during pregnancy, often because of their concerns about possible teratogenic effects.…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few comparable studies on LT4 use during pregnancy. A Danish study showed an increase in LT4 use among pregnant women between 1997 and 2010 [20]. However, the authors reported that <1% of pregnant women received LT4 medication, and this proportion is significantly lower than the estimated rate of hypothyroidism in pregnant women (about 2.8%) [20].…”
Section: Discussionmentioning
confidence: 98%
“…[9][10][11][14][15][16][17] We found no difference in fine and gross motor function, communication skills, and behavior. This is important because some women discontinue their THRT upon recognition of pregnancy 37,38 and, among those who are medicated, adherence to THRT is not always optimal. 39 Juch et al 39 found that 17% of pregnant women with hypothyroidism exhibit low adherence during pregnancy.…”
Section: Discussionmentioning
confidence: 99%